Effect of a pager notification system on Australasian Triage Scale category 2 patients in a paediatric emergency department. (19th May 2016) - Cheng, Daryl R; McCartney, Laura E; West, Adam; Craig, Simon S
Abstract: Objective: Australasian EDs have introduced innovative processes to ensure safe and timely management of patients. Our ED introduced a dedicated pager system to provide rapid assessment of Australasian Triage Scale (ATS) category 2 patients in an attempt to expedite ED care. The present paper aims to evaluate the impact of this initiative on time to clinician, ED length of stay (LOS) and clinical outcomes in a tertiary paediatric ED. Methods: Retrospective structured chart review on patients presenting in a 2 month period before the intervention (August–September 2009) and the same time 1 year later. Patients were grouped into common ATS category 2 presentations and analysed in these subcategories. Clinical indicators of appropriate and timely performance were selected from best practice performance guidelines. Results: 779 ATS category 2 patients were seen during the two periods: 370 pre‐intervention and 409 post‐intervention. The overall percentage of ATS category 2 patients seen within the target time increased by 22.3%, although there was no significant change in ED LOS. The median time for patients from triage to being seen by an ED clinician improved from 10 to 6 min ( P < 0.01). However, we were unable to demonstrate an impact of the pager system on various clinical quality indicators. Conclusions: The rapid assessment pager system proved beneficial in reducing triage to clinician times for ATS category 2 patients but showed no improvement in overall ED LOS or disease‐specific clinical quality indicators. Further research is needed to determine the influence of other components of ED functioning on clinical outcomes, as well as the overall clinical impact a pager system has on other measures of quality such as patient satisfaction and other subgroups of patients.